Missed opportunities to advance knowledge on traffic safety: Accessibility of driver licensing and crash data for scientific research. (May 2020) - Carey, Meghan E.; Anderson, Evan D.; Mansour, Rania; Sloan, Jason; Curry, Allison E.
Highlights: Review of state legal text to characterize release of driver license and crash data. 37 states and D.C. authorize release of individual-level licensing data. Disconnect between authorized release of licensing data and limited use in research. Largely unclear if individual-level crash data is accessible in existing statutes. Abstract: Objective: Identifiable individual-level driver licensing and motor vehicle crash data are essential to advancing transportation safety research. However, epidemiologic studies using such data are rare, which may reflect their inaccessibility. We conducted a legal mapping study to evaluate US state laws regulating access to driver licensing and motor vehicle crash data for use in scientific research. Methods: Legal statutes regulating the release of driver licensing and motor vehicle crash data for all 50 US states and the District of Columbia (D.C.) were retrieved. Legal text was evaluated to determine whether these jurisdictions authorize release of identifiable individual-level licensing and crash data for use in non-governmental research. Results: Thirty-six states and D.C. explicitly authorize release of identifiable individual-level licensing data to researchers. Only five states and D.C. authorize release of identifiable individual-level crash records. No states explicitly prohibit the release of individual-level data about licensing records and only three states prohibit release of individual-level crash record data, meaning that in many states it is ambiguous whether and when releasing such data to researchers is permitted. Conclusions: It is important to understand why licensing data are not used more frequently in transportation safety research given that many state laws permit access for non-governmental researchers. Reforming state laws to clarify and increase access to identifiable individual-level crash report data is an important priority for transportation safety advocates and researchers.